Innovative Work Behavior of Catholic High School Teacher In Manado City - Ketsia Theresia Zeke; Herry Sumual; Cosmas Poluakan; Jeffry S J Lengkong (Green Publisher Indonesia, 2022)
This study aims to explain the influence of exemplary leadership, creative climate, collective trust, and commitment to teachers' innovative work behavior. The research method used is a survey. The research sample consisted of 100 teachers spread across five Catholic Senior High Schools (SMA) located in Manado City. The research data were collected using a questionnaire technique and analyzed using descriptive and inferential statistical techniques. Based on the results of the study, it shows that both individually and simultaneously, exemplary leadership, creative climate, collective trust, and commitment have a positive and significant effect on teachers' innovative work behavior. The results of the research were discussed and conclusions were drawn as well as suggestions for future research on teachers' innovative work behavior.